Exploring Single-Atom Nanozymes Toward Environmental Pollutants: Monitoring and Control - Wu, Guojian; Li, Si; Luo, Linpin; Li, Yuechun; Zhang, Wentao; Wang, Heng; Liu, Sha; Du, Chenxing; Wang, Jianlong; Cheng, Jie; Wu, Yongning; Shen, Yizhong (Nano-Micro Letters, 2025)
As environmental pollutants pose a serious threat to socioeconomic and environmental health, the development of simple, efficient, accurate and cost-effective methods for pollution monitoring and control remains a major challenge, but it is an unavoidable issue. In the past decade, the artificial nanozymes have been widely used for environmental pollutant monitoring and control, because of their low cost, high stability, easy mass production, etc. However, the conventional nanozyme technology faces significant challenges in terms of difficulty in regulating the exposed crystal surface, complex composition, low catalytic activity, etc. In contrast, the emerging single-atom nanozymes (SANs) have attracted much attention in the field of environmental monitoring and control, due to their multiple advantages of atomically dispersed active sites, high atom utilization efficiency, tunable coordination environment, etc. To date, the insufficient efforts have been made to comprehensively characterize the applications of SANs in the monitoring and control of environmental pollutants. Building on the recent advances in the field, this review systematically summarizes the main synthesis methods of SANs and highlights their advances in the monitoring and control of environmental pollutants. Finally, we critically evaluate the limitations and challenges of SANs, and provide the insights into their future prospects for the monitoring and control of environmental pollutants. Highlights: 1 Review of the state-of-the-art synthesis strategies for single-atom nanozymes. 2 Analysis of the recent advances in single-atom nanozymes for monitoring and control of environmental pollutants. 3 Challenges and perspectives of single-atom nanozymes in environmental pollutants monitoring and control.